2017
DOI: 10.3177/jnsv.63.244
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Myostatin-Targeting siRNA and ActRIIB-Fc Fusion Protein Increases Masseter Muscle Mass and Fiber Size

Abstract: Summary Myostatin, a member of the TGF-␤ superfamily, is a negative regulator of skeletal muscle cell growth and differentiation, and binds with high affinity to the activin type IIB receptor (ActRIIB). The soluble ligand-binding domain of ActRIIB fused to the Fc domain of IgG (ActRIIB-Fc) potently binds and inhibits TGF-␤ family members in muscle, leading to rapid and marked muscle growth. The present study was designed to assess the effectiveness of the co-delivery of myostatin-targeting siRNA (Mstn-siRNA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…GDF8 is highly homologous to GDF11 (~90%) (33) and overlaps in function with GDF11 and activin A in regulating muscle mass and myocyte hypertrophy based on genetic loss-of-function and pharmacologic experiments (34,35). Targeting GDF8, GDF11, and activin ligands as a group versus individually has proven to be more effective for increasing muscle mass (36)(37)(38). By analogy, it is likely that this set of ligands of ACTRIIA may have overlapping roles in pulmonary vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…GDF8 is highly homologous to GDF11 (~90%) (33) and overlaps in function with GDF11 and activin A in regulating muscle mass and myocyte hypertrophy based on genetic loss-of-function and pharmacologic experiments (34,35). Targeting GDF8, GDF11, and activin ligands as a group versus individually has proven to be more effective for increasing muscle mass (36)(37)(38). By analogy, it is likely that this set of ligands of ACTRIIA may have overlapping roles in pulmonary vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated surgical role of atelocollagen and promising clinical results have been reported [8,16,21,23,25]. In a recent study using atelocollagen in orthopaedic surgery, Suh et al [26] suggested repair after using patch-type atelocollagen between the torn rotator cuff and bone using rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Highly purified atelocollagen is low in immunogenicity because it is free from telopeptides and has many advantages for biocompatibility and optimizing collagen-cell interaction for efficacy and lower side effects [7]. Studies using human subjects and experimental animals have shown that atelocollagen provides good therapeutic results by promoting cell proliferation and early epithelialization while causing little rejection and few complications [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is estimated that PAC might have acted as a scaffold to facilitate the tissue regeneration reaction around damaged tissue in the present study. In this respect, it is possible that using progenitor cells or proliferation-related factors may have a synergistic effect [19,24,25]. Finally, the effect might have been caused by the reduction of inflammation.…”
Section: Discussionmentioning
confidence: 99%